Manner Modifiers as Syntactic Heads - Bogren Svensson, Victor (Centre for Languages and Literature, Lund University, 2023)
The present dissertation concerns typologically unusual ways of encoding manner information, namely verbal affixes (manner affixes), incorporated constituents (incorporated manner modifiers) and auxiliary verbs (manner adverbial verbs). A key proposal is that all three are overt realizations of syntactic heads merged in the clausal spine, thereby presenting novel data that can be used to probe into the relationship between morphology and syntax.Fieldwork data from West Greenlandic forms the basis of the discussion of manner affixes (chapter 3). This study was complemented by a typological survey of languages with manner affixes and incorporated manner modifiers (chapter 4). The study of manner adverbial verbs was based on linguistic fieldwork on Takituduh Bunun, and on already published data on other Austronesian languages spoken on Taiwan (chapter 5).I show that these manner modifiers are limited to a low position in the clausal spine, which is reflected in their linear order in relation to other functional categories merged in the clausal spine (TAM, negation, valency changing morphology), both on a word and clausal level. The hierarchical position of these manner modifiers in West Greenlandic and Takituduh Bunun exhibits limited but productive variation, which is reflected in linear order and scope interpretation. This constitutes novel arguments against a cartographic conception of the clausal spine, instead favouring a conception of the clausal spine as divided into distinct sortal domains that constrain the distribution of functional categories, but that still allow for a degree of variation in hierarchical ordering within the different sortal domains. Novel statistical implicational universals are also presented, covering both the semantic and morphosyntactic properties of manner affixes and incorporated manner modifiers.